Development and Validation of RP-High Performance Liquid Chromatographic Method for Simultaneous Estimation of Teneligliptin and Pioglitazone In Tablet Formulation - Vinay T; Lalitha N; Mubeen G (Asian Journal of Pharmaceutical Research and Development, 2024)
A reliable, economical, sensitive and reproducible RP-HPLC was developed and validated for the simultaneous estimation of Teneligliptin (TENE) and Pioglitazone (PIO) in combined dosage form. In the RP-HPLC method the mobile phase used was Acetonitrile: 5mM potassium dihydrogen orthophosphate (KH2PO4) buffer (60:40) at PH 3.6 and flow rate was 1.0 ml per min. The method was scanned at isosbestic point 238 nm for both the drugs. The linearity range for TENE and PIO was found to be 0.1-500 µg/ml and 0.500 µg/ml with regression correlation coefficient of (R2) 1.000 and 0.999 respectively. The LOD and LOQ for TENE was found to be 0.002645 and 0.0801 and for PIO was found to be 0.017727 and 0.05371 respectively. The retention time for Teneligliptin andPioglitazone was found to be 2.678 min and 5.010 min respectively. The percentage Assay for TENE and PIO was found to be 97.90-100.69%w/w and 98.53-99.58% w/w respectively. The developed method RP-HPLC was validated as per ICH guidelines.